2019
DOI: 10.1530/vb-19-0024
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and vascular protection

Abstract: Ghrelin is a small peptide with important roles in the regulation of appetite, gut motility, glucose homeostasis as well as cardiovascular protection. This review highlights the role that acyl ghrelin plays in maintaining normal endothelial function by maintaining the balance of vasodilator-vasoconstrictor factors, inhibiting inflammatory cytokine production and immune cell recruitment to sites of vascular injury and by promoting angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…In this study, we provide direct evidence that hexarelin act as a vasodilator in the healthy rat coronary microcirculation, and that this involved activation of the GHS-R1a receptor pathway as reported for ghrelin (Pearson et al, 2019). Furthermore, for the first time in a PH model, we show that: (1) more myosin heads appeared to become super-relaxed, with displacement away from actin binding sites, while (2) myosin interfilament spacing at diastole was additively reduced by the combination of PH and chronic hexarelin treatment.…”
Section: Discussionsupporting
confidence: 70%
“…In this study, we provide direct evidence that hexarelin act as a vasodilator in the healthy rat coronary microcirculation, and that this involved activation of the GHS-R1a receptor pathway as reported for ghrelin (Pearson et al, 2019). Furthermore, for the first time in a PH model, we show that: (1) more myosin heads appeared to become super-relaxed, with displacement away from actin binding sites, while (2) myosin interfilament spacing at diastole was additively reduced by the combination of PH and chronic hexarelin treatment.…”
Section: Discussionsupporting
confidence: 70%
“…Similar to our study, some studies have shown that ghrelin can inhibit vascular endothelial cell angiogenesis [ 30 , 31 ]; however, other studies have found opposite results suggesting that ghrelin can boost angiogenesis [ 32 , 33 ]. Taking these findings together, we hypothesized that ghrelin has a protective effect on vascular endothelial cells [ 34 ] and maintains cellular homeostasis under pathological conditions by regulating—either promoting or inhibiting—angiogenesis [ 15 ], for cells to better adapt to the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin is produced by the stomach, heart, lung, and kidney and has extensive physiological effects, such as stimulating growth hormone secretion, promoting food intake, and maintaining energy homeostasis. Emerging evidence has shown favorable effects of ghrelin on cardiovascular function via either growth hormone-dependent or -independent mechanisms [ 116 , 117 ].…”
Section: Vasoactive Peptides and Vascular Aging-related Diseasesmentioning
confidence: 99%
“…Emerging evidence has shown favorable effects of ghrelin on cardiovascular function [ 116 , 117 ]. Ghrelin rescued the activity of SIRT1 and the expression of superoxide dismutase-2 (SOD-2), a primary enzymatic antioxidant defense against ROS production, and resulted in great attenuation of EC senescence in mice [ 119 ].…”
Section: Vasoactive Peptides and Vascular Aging-related Diseasesmentioning
confidence: 99%